1991
DOI: 10.1017/s0014479700018998
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tied Ridge Cultivation on the Yield of Maize and a Maize/Cowpea Relay in the Gambia

Abstract: The growing season in the semi-arid region of West Africa is drought prone and of irregular duration. Two experiments were conducted in 1986 and 1987 to test the effects of flat cultivation and tied ridge cultivation (TRC) on the yields of maize and the component crops of a maize and cowpea relay cropping system. The two research sites, with slopes of 0.05% and 3%, were near Sapu, The Gambia, on an Aridic Kandiustalf in the 700 mm rainfall zone.Both growing seasons had above average rainfall. In both years, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…Therefore, farmers should use this in situ rainwater harvesting (tied ridges) method in their scattered fields to reduce harvest losses and to manage the high rainfall variability. Elsewhere in semiarid areas, the practice has been successful for other cereals, such as maize [38][39][40] and sorghum [2,39]. However, in our study, we found that tied ridges increased spatial yield variability.…”
Section: Discussioncontrasting
confidence: 63%
“…Therefore, farmers should use this in situ rainwater harvesting (tied ridges) method in their scattered fields to reduce harvest losses and to manage the high rainfall variability. Elsewhere in semiarid areas, the practice has been successful for other cereals, such as maize [38][39][40] and sorghum [2,39]. However, in our study, we found that tied ridges increased spatial yield variability.…”
Section: Discussioncontrasting
confidence: 63%
“…Under MD, optimum yields are obtained under temperature increases of +1.0 • C and changes in precipitation of +30%. Thus, in cases of high temporal rainfall variability, as in our case study site, it is advised that farmers adopt infield rainwater harvesting, such as tied ridges [25,44,45,[53][54][55], since they prolonging soil moisture. Although alternatives like providing irrigation may be effective, not only do these require further investigation regarding cost-benefit advantages, but these also may come with insurmountably high initial investment costs [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Contour strips (ridges) and tied ridges Kenya [27,101], Gambia [102], Tanzania [103], Ethiopia [92,104], Nigeria [105] Contour strips and tied ridges decrease soil erosion, enhance groundwater recharge and prolong soil moisture availability…”
Section: Use Of Groundwatermentioning
confidence: 99%
“…Tied ridges provide a better crop growth environment [102,148,149] in areas where the temporal rainfall variability is a challenge. Evidence of higher cereal yields and increased rain water use efficiency [27,101], and even better income [92,104], have been reported.…”
Section: Contour Ridges and Tied Ridgesmentioning
confidence: 99%
See 1 more Smart Citation